2021
DOI: 10.1111/bcp.14772
|View full text |Cite
|
Sign up to set email alerts
|

A randomized single and multiple ascending dose study in healthy volunteers of LTI‐291, a centrally penetrant glucocerebrosidase activator

Abstract: A mutation in the GBA1 gene is the most common genetic risk factor for developing Parkinson's disease. GBA1 encodes the lysosomal enzyme glucosylceramidase beta (glucocerebrosidase, GCase) and mutations decrease enzyme activity. LTI-291 is an allosteric modulator of GCase, enhancing its activity. These first-in-human studies evaluated the safety, tolerability, pharmacokinetics and pharmacodynamics of single and multiple ascending doses of LTI-291 in healthy volunteers.Methods: In the single ascending dose (SAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…This includes compounds that promote activity or trafficking of the lysosomal enzyme GBA (e.g., LTI-291, LNK-754) [ 50–52 ] and small molecules that reduce the synthesis of glucosylceramide (e.g., venglustat), the substrate of GBA, which can reduce SNCA pathology in PD patient iPSC-derived neuronal cultures and in vivo [ 52–55 ].…”
Section: Introductionmentioning
confidence: 99%
“…This includes compounds that promote activity or trafficking of the lysosomal enzyme GBA (e.g., LTI-291, LNK-754) [ 50–52 ] and small molecules that reduce the synthesis of glucosylceramide (e.g., venglustat), the substrate of GBA, which can reduce SNCA pathology in PD patient iPSC-derived neuronal cultures and in vivo [ 52–55 ].…”
Section: Introductionmentioning
confidence: 99%
“…LTI-291 is an allosteric modulator of GBA that enhances its activity. The results of a phase 1 trial have been published and showed that LTI-291 is well tolerated (36). According to an announcement on October 1, 2020, on the company's homepage (https://www.bial.com/com/, accessed on September 19, 2021), a phase 2 trial should be ready to start in 2021.…”
Section: ) Lti-291mentioning
confidence: 99%
“…The effects of the GCase enzyme activator LTI291 were studied in a 1-month phase Ib trial, and around 40 GBA-PD patients took part in the study. No adverse events were reported, and the findings showed that the drug had good dose-dependent brain penetration [ 220 ].…”
Section: Novel Therapeutic Strategies In Pd Managementmentioning
confidence: 99%